Desenvolvimento de tecnologia para processamento mínimo de inhame - Brito, Thaís Trindade de (2011)
This work aimed to develop the minimal processing technology of yam and to verify the efficiency of the use of antioxidants in the prevention of enzymatic darkening of the product. Initially were defined the best conditions to establish the flowchart stages for minimally processed yam through sensory analysis to establish the type of cut (cube or okra), the sanitizer concentration of active chlorine (100 mgL-1 ,150 mgL-1 and 200 mgL-1 ) and technique for removal the excess of water (centrifugation or rinsing). This research also evaluated the efficiency of different antioxidants (ascorbic acid 1%, citric acid 1% and EDTA 1%) at rinse stage and types of packaging (nylon poly with and without vacuum and polystyrene covered with PVC film) in the prevention of enzymatic darkening in minimally processed yam during the refrigerated storage. For the refrigerated storage study, it were determined the browning index, pH, soluble solids content (°Brix), phenol concentration, titratable acidity, polyphenoloxidase activity (PPO), microbiological and sensory evaluation. During this period, minimally processed yam samples packaged with nylon poly under vacuum treated with ascorbic acid presented the bests results in relation to the studied characteristics until de 15th day of storage. Thus the stages of minimal processing of yam are: okra cuts with approximately 3 cm thickness, sanitizing with 200 mgL-1 of active chlorine, rinse with ascorbic acid 1%, rinsing, packaging with nylon poly under vacuum and storage at refrigerated temperature (5± 2 °C) for 15 days.